Assessing effects of thinning on the stem form in larch during the stand initiation and stem exclusion stages using terrestrial laser scanning - Dandan Li; Dandan Li; Weiwei Jia; Weiwei Jia; Fengri Li; Fengri Li; Haotian Guo; Haotian Guo; Fan Wang; Fan Wang; Xiaoyong Zhang; Xiaoyong Zhang (Frontiers in Forests and Global Change)
Forest management is vital to the growth and development of trees at different stages. However, comprehensively capturing tree attributes to determine the response to management remains a major challenge. Therefore, this study utilized TLS technology to probe forest structure information, explore the effects of TLS on stem diameter, and develop the most appropriate taper model to reveal how thinning management affects the stem size and form of larch during SIS and SES. Larch plantations aged 16 and 26 years were subjected to different intensities of thinning treatments, and 3D structural information of the stems was measured via TLS in the 7th year after the intervention. In present study, age and thinning intensity were used as dummy variables to reduce modeling costs and taper models were developed to reflect the stem shape. ANOVA was applied to assess differences in tree attributes (slenderness, stem taper, form factor at breast height, and form quotient) among the different thinning treatments. The results showed that the ability of TLS to measure stem diameter information was related to forest conditions, and the effect of the SES with low stand density and large stem diameters was greater than that of the SIS with complex understory conditions and small stem diameters (with 70% of the stem diameter captured in the SIS and 80% in the SES). During the SIS, plants were more sensitive to thinning, and their diameter growth efficiency was significantly greater than that during the SES. Thinning promoted trunk growth in the bottom part and intermediate section compared to that in the unthinned plots. The average DBH increased with increasing thinning intensity, while slenderness exhibited the opposite pattern. The responses of TH and form factor at breast height to thinning were not significant, but they were age dependent. Since TLS has difficulty capturing the diameter of canopy height, the Kozak variable-exponent taper equation is more suitable for modeling stem forms, and setting age as well as thinning intensity as dummy variables is an efficient modeling method. Overall, TLSs can be used for measuring long-term tree responses after intervention to efficiently support nondestructive forest inventories and management.